E–Business: Teknologi dan Peluang Bisnis di Indonesia - Chandra Wibowo Widhianto (Bina Nusantara University, 2002)
Information technology offers creativity and business inovation rapidly and easily. A business must see the new opportunity. Microsoft give solution that will “spoil” business man in implementation, management, and the exploitation of the information technology maximally. The information technology is cheap and easy to applied now.